2017
DOI: 10.1080/15476286.2016.1269999
|View full text |Cite
|
Sign up to set email alerts
|

Increased complexity of circRNA expression during species evolution

Abstract: Circular RNAs (circRNAs) are broadly identified from precursor mRNA (pre-mRNA) back-splicing across various species. Recent studies have suggested a cell-/tissue- specific manner of circRNA expression. However, the distinct expression pattern of circRNAs among species and its underlying mechanism still remain to be explored. Here, we systematically compared circRNA expression from human and mouse, and found that only a small portion of human circRNAs could be determined in parallel mouse samples. The conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
164
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 25 publications
5
164
0
Order By: Relevance
“…What factors contribute to the survival of circRNA during hybridization and polyploidization? Recent research in the comparison of human and mouse circRNA found that circRNAs across species usually exhibit higher conservation in primary sequences and longer length of flanked introns . In our study, we also observed this phenomenon.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…What factors contribute to the survival of circRNA during hybridization and polyploidization? Recent research in the comparison of human and mouse circRNA found that circRNAs across species usually exhibit higher conservation in primary sequences and longer length of flanked introns . In our study, we also observed this phenomenon.…”
Section: Discussionsupporting
confidence: 85%
“…In a previous study, it was found that 15% of cir-cRNAs in humans and 40% in mouse are conserved [38]. Another study found that~30% of circRNA is conserved in the mouse and rat genomes, and~10% is conserved across human, mouse and rat genomes [22].…”
Section: Features Of Conserved Circrna In Cottonmentioning
confidence: 97%
“…Thus, the inhibition of miRNA on target was eliminated and the number of target genes was increased. This mechanism is called the competitive endogenous RNA (ceRNA) mechanism . The RNAs research found that circRNAs play a key role in the development of the disease like EH.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, at least two types of circular RNAs are processed from nuclear (m)RNA precursors through the spliceosomal pathway [4], including circular intronic RNAs (ciRNAs) [5] from excised introns and circular RNAs (circRNAs) [6][7][8][9][10] from back-spliced exon(s) (reviewed in [1,4]). By taking advantage of nonpolyadenylated transcriptome enrichment [11][12][13] and specific computational approaches that identify reads mapped to back-splice junction sites with a reversed genomic orientation ( Figure 1A) [10,15,16] (reviewed in [1,2,17]), a large amount of circRNAs have been recently re-discovered from thousands of gene loci in various cell lines/tissues and across different species [6][7][8]10,[18][19][20][21]. Increasing lines of evidence have suggested that circRNAs could play important roles in gene expression regulation with different mechanisms of action (reviewed in [1]).…”
Section: Introductionmentioning
confidence: 99%